The India-Pakistani Military and Nuclear Arms Race in Post-Cold War Period: The Regional Security Complex in South Asia - Arfin Sudirman (Global Strategis, 2018)
The article examines the India-Pakistani nuclear arms race and its effect to the regional security in South Asia today as a Cold War’s legacy. By using regional security complex theory and qualitative method, this article argues that the balance of power and security dilemma principles also work in the region level due to the fact that both countries use nuclear weapons as a deterrence power, a similar pattern that also occurred during the Cold War era. External power such as US, China and Russia are actually aggravating the situation by selling the nuclear material (such as uranium) and technology to both countries regardless the future consequence. However, since multipolar system gives level of threat into more complex and broader sectors of security issues-not to mention the existence of non state actors such as terrorist groups, the regional security in South Asia is essential to prevent further damage to the nearby region. Therefore, the role of international community such as the UN to restore order in the regions is vital.